Healthy Hearts for an Abundant Life: Feasibility of a Culturally Adapted Cardiovascular Disease Prevention Curriculum for African American Women (Mary Ann Liebert, 2021)
Background: This study tested the feasibility of implementing Healthy Hearts for an Abundant Life (HHAL), a cultural adaptation for African American (AA) women of the evidence-based cardiovascular disease prevention program Strong Women-Healthy Hearts (SWHH). Methods: Using a quasi-experimental pre-post study design, this 12-week program was implemented in four faith-based organizations between 2017 and 2018. Eligible participants were AA women between 40 and 65 years who had a body mass index of 25 or higher and were currently sedentary. HHAL program participants met weekly for 2-h sessions led by program leaders. The curriculum has four modules: total health; relationships, family, and networks; material security and the environment; and emotional wellness. Each class included walking for 30?min, goal-setting session, and a group dialog called ?making it work? for building collective efficacy. Results: Of the 27 participants (mean age=54.2?5.9), 24 completed postassessments (93% retention rate). All outcome measures proved feasible and weekly program attendance was 73%. Findings from in-depth interviews show high satisfaction with the program and suggest extending the class time and adding cooking demonstrations. Conclusions: The culturally adapted HHAL proved feasible and was positively received by the participants. Future studies will evaluate the effectiveness of the program.